Service Quality Model for IPTV Service: Identification of Key Features and Their Relationships - Kim, Kwang-Jae; Shin, Wan-Seon; Min, Dae-Kee; Kim, Hyun-Jin; Yoo, Jin-Sung; Lim, Hyun-Min; Lee, Soo Ha; Jeong, Yong-Kee (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
Because of the rapid growth of the service sector, an effective and systematic methodology for quality analysis and improvement is increasingly important. An IPTV service provides various contents on demand via TV and set-top box with Internet line. Its global market size is rapidly growing, but there is a lack of systematic analysis about IPTV service quality. This paper aims to develop an IPTV service quality model and identify key features and their relationships. The quality function deployment (QFD) method is applied in two phases. The results of QFD application are analyzed, and key features and their relationships are identified. Moreover, scenarios for applying the analysis to improve IPTV service quality are developed for IPTV service providers. As the analysis provided is general and is applicable to other services, this paper provides insights into improving service quality, not only for ITPV service providers, but also for service providers in many kinds of industries.